ОРГАНІЗАЦІЯ ЗАКОРДОННИХ СТАЖУВАНЬ У ПРОЦЕСІ ПІДГОТОВКИ ФАХІВЦІВ СФЕРИ ТУРИЗМУ - H.P. Shchuka, G (Continuing Professional Education: Theory and Practice, 2019)
The article describes the question of organization of internships abroad for students of tourist specialities as a form of industrial practice. Common issues that arise during the internship were identifi ed on the basis of experience in the Ukrainian institutions of higher education, the ways to prevent and eliminate the preparatory, and fi nal production stages were identifi ed too.